Glucose‐6‐Phosphate Dehydrogenase from the Oleaginous Microalga Nannochloropsis Uncovers Its Potential Role in Promoting Lipogenesis. Issue 2 (9th October 2019) - Xue, Jiao; Chen, Ting‐Ting; Zheng, Jian‐Wei; Balamurugan, Srinivasan; Liu, Yu‐Hong; Yang, Wei‐Dong; Liu, Jie‐Sheng; Li, Hong‐Ye
Abstract: Microalgae have long been considered as potential biological feedstock for the production of wide array of bioproducts, such as biofuel feedstock because of their lipid accumulating capability. However, lipid productivity of microalgae is still far below commercial viability. Here, a glucose‐6‐phosphate dehydrogenase from the oleaginous microalga Nannochloropsis oceanica is identified and heterologously expressed in the green microalga Chlorella pyrenoidosa to characterize its function in the pentose phosphate pathway. It is found that the G6PD enzyme activity toward NADPH production is increased by 2.19‐fold in engineered microalgal strains. Lipidomic analysis reveals up to 3.09‐fold increase of neutral lipid content in the engineered strains, and lipid yield is gradually increased throughout the cultivation phase and saturated at the stationary phase. Moreover, cellular physiological characteristics including photosynthesis and growth rate are not impaired. Collectively, these results reveal the pivotal role of glucose‐6‐phosphate dehydrogenase from N. oceanica in NADPH supply, demonstrating that provision of reducing power is crucial for microalgal lipogenesis and can be a potential target for metabolic engineering. Abstract : Though heterologous recombineering strategy holds great potential in imparting oleaginicity in fast‐growing algal species, recruitment of key metabolic candidate has emerged as the critical determinant due to the multi‐layer regulation of lipogenesis. Here, the authors interrogated the efficacy of pentose phosphate pathway on providing lipogenic NADPH by expressing heterologous glucose‐6‐phosphate dehydrogenase (G6PD) from N. oceanica in C. pyrenoidosa . The results uncovered that NoG6PD expression remarkably increased G6PD activity towards lipogenesis and exemplified a potential metabolic target in perturbing intricate lipogenesis in heterologous alga.